2017
DOI: 10.1088/1742-6596/863/1/012063
|View full text |Cite
|
Sign up to set email alerts
|

α clustering and its connection to the E1 response of heavy nuclei

Abstract: Abstract. The generation of the collective nuclear E1 response is intimately connected to the breaking of proton-neutron symmetry. In this contribution, we present our recent results on a possible α-cluster dipole mode, which were obtained in the framework of the spdf interacting boson model. These extended studies of the low-lying E1 response support the general occurence of α-cluster dipole states in atomic nuclei.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Besides the theoretical strength which is generated by an E1 excitation to the state at 3146 keV with n p /n f = 0.18, all signficant E1 strength above 2 MeV is caused by two states with n p /n f > 1 at 2238 keV and 3221 keV, respectively. In two of our previous publications, we have shown that states with n p /n f > 1 might be connected to α-clustering in rareearth [72] and A < 100 nuclei [73]. The E1 strength built upon the ground state in the actinides might as well be generated by the p-boson, i.e.…”
Section: B Octupole Excitations or α-Clustering?mentioning
confidence: 81%
“…Besides the theoretical strength which is generated by an E1 excitation to the state at 3146 keV with n p /n f = 0.18, all signficant E1 strength above 2 MeV is caused by two states with n p /n f > 1 at 2238 keV and 3221 keV, respectively. In two of our previous publications, we have shown that states with n p /n f > 1 might be connected to α-clustering in rareearth [72] and A < 100 nuclei [73]. The E1 strength built upon the ground state in the actinides might as well be generated by the p-boson, i.e.…”
Section: B Octupole Excitations or α-Clustering?mentioning
confidence: 81%